27 Animation supported consent in patients with acute coronary syndrome transferred for urgent angiography and angioplasty. (17th July 2020) - Wald, David; Casey-Gillman, Ollie; Comer, Katrina; Mansell, Josephine; Teoh, Howie; Mouyis, Kyriacos; Kelham, Matthew; Chan, Fiona; Ahmet, Selda; Sayers, Max; McCaughan, Vincent; Polenio, Nito
Abstract : Introduction: Patient understanding of angiography and angioplasty is often incomplete at the time of consent. Language barriers and time constraints are significant obstacles, particularly in the urgent setting, where the procedures are unplanned. We introduced digital animations to support consent for inter-hospital transfer patients with acute coronary syndromes and assessed the effect of on patient understanding. Methods: Multi-language animations explaining angiography and angioplasty, (www.explainmyprocedure.com/heart) were introduced at nine district hospitals for patients with acute coronary syndrome (non-ST elevation myocardial infarction and unstable angina) before urgent transfer to a cardiac centre for their procedure. Patients watched the animations on wards using personal devices or internet-free videobooks. Reported understanding of the reason for transfer, the procedure, its benefits and risks in 100 consecutive patients were recorded before introduction of the animations into practice (no animation group) and in 100 consecutive patients after their introduction (animation group). Patient understanding in the 2 groups was compared. Figure 1 shows a flow diagram of the pathway. Results: Table 1 shows the characteristics of patients in the animation and no animation groups. Following introduction, 83/100 patients reported they had watched the animation before inter-hospital transfer (3 declined and 14 were overlooked). The proportions of patients who understood the reason for transfer, the procedure, its benefits and risks, in the no animation group (n=100) were respectively, 58%, 38%, 25% and 7% and in the animation group (n=100), 85%, 81%, 73% and 61% (p<0.001 for all comparisons, figure 1 ). Conclusion: Use of animations explaining angiography and angioplasty is feasible before urgent inter-hospital transfer and was associated with about a 2-fold improvement in understanding of the benefits and a 9-fold improvement in understanding of the risks. The approach is not limited to cardiology and has the potential to be applied to all specialties in medicine. Conflict of Interest: Founder of Explain my Procedure